2015
DOI: 10.1016/j.clinimag.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic olivary degeneration resulting from posterior fossa masses and their treatments

Abstract: Purpose Characterize hypertrophic olivary degeneration (HOD) that develops from posterior fossa masses and their treatments. Methods Retrospectively reviewed MR images and clinical data of 10 patients with posterior fossa masses and HOD. Results Eight patients had cerebellar lesions, and two patients had pontine lesions. Lesions consisted of tumors, demyelination, and nonspecific necrosis. MRI showed T2 hyperintense signal in the inferior olive a median 86 days after the diagnosis of a posterior fossa lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Figure 2 illustrates that all but one case of HOD followed the causal hypothesis of a HOD causing a lesion within the dentato-rubro-olivary-pathway and its unidirectional orientation. Conclusively, no HOD was found in the literature with damage to the efferent olivocerebellar fibers, which do not functionally affect the olive itself [10,15]. One case was MR-negative, which could be explained either by a small radiotherapeutic lesion below the 3 Tesla detection threshold or between MRI slices, or the presence of idiopathic, non-traumatic HOD.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Figure 2 illustrates that all but one case of HOD followed the causal hypothesis of a HOD causing a lesion within the dentato-rubro-olivary-pathway and its unidirectional orientation. Conclusively, no HOD was found in the literature with damage to the efferent olivocerebellar fibers, which do not functionally affect the olive itself [10,15]. One case was MR-negative, which could be explained either by a small radiotherapeutic lesion below the 3 Tesla detection threshold or between MRI slices, or the presence of idiopathic, non-traumatic HOD.…”
Section: Discussionmentioning
confidence: 89%
“…However, none of the patients in this study showed any signs of HOD on MRI acquired within 3 months prior to surgery. In a recent case series, Hirano et al suggested that HOD develops either primarily as a result of the tumor mass itself, or secondarily as a result of treatment [15]. Hirano et al also included patients with posterior fossa masses of non-tumor origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this could not be proven in a study of OT patients 98. Additionally, the intriguing findings of Gallea et al, notably hypertrophy of the cerebellar vermis and SMA in OT, may be akin to the hypertrophy of the inferior olive in patients with lesions within various locations of the dentatorubral tract or central tegmental tract (Guillain–Mollaret triangle)100 and reflect that there are potentially multiple OT generators within cerebellothalamocortical pathways.…”
Section: Resultsmentioning
confidence: 94%